2020
DOI: 10.3928/1081597x-20200820-01
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Epithelium-off Corneal Cross-linking With High Ultraviolet Energy Dose (7.2 J/cm 2 ) for Progressive Keratoconus: 2-Year Results in a Chinese Population

Abstract: PURPOSE: To evaluate the results of epithelium-off continuous light accelerated corneal cross-linking (CXL) with a total dose of 7.2 J/cm 2 for treating progressive keratoconus in a Chinese population during 24 months of follow-up. METHODS: In this retrospective, interventional case series, 45 eyes of 31 consecutive patients with progressive keratoconus were evaluated. All patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Actualmente, la tendencia en el manejo del queratocono es detener su progresión lo más temprano posible para no tener que llegar a un trasplante de córnea. En los últimos años han surgido técnicas con esa finalidad, entre ellas el cross-linking, que con sus diferentes variantes [15][16][17] busca estabilizar el queratocono mediante la impregnación de riboflavina, seguida de la aplicación de radiación ultravioleta para que así el estroma de la córnea reaccione y genere puentes entrecruzados en las fibras de colágena de este [18][19][20][21] . En cuanto a la reducción del poder de las queratometrías, así como de la refracción, la técnica de cross-linking ha mostrado poco efecto 17 .…”
Section: Discussionunclassified
“…Actualmente, la tendencia en el manejo del queratocono es detener su progresión lo más temprano posible para no tener que llegar a un trasplante de córnea. En los últimos años han surgido técnicas con esa finalidad, entre ellas el cross-linking, que con sus diferentes variantes [15][16][17] busca estabilizar el queratocono mediante la impregnación de riboflavina, seguida de la aplicación de radiación ultravioleta para que así el estroma de la córnea reaccione y genere puentes entrecruzados en las fibras de colágena de este [18][19][20][21] . En cuanto a la reducción del poder de las queratometrías, así como de la refracción, la técnica de cross-linking ha mostrado poco efecto 17 .…”
Section: Discussionunclassified
“…Our findings showed that RMS total was not statistically significantly different between the two groups at all time points. Kang et al 58 demonstrated that, after A-CXL with high UVA energy dose (7.2 J/cm 2 ) particularly, total root mean square and higher order aberrations improved at 12 to 24 months after CXL.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the seven studies (71.4%) that evaluated UDVA noted statistically significant improvements [20,22,23,26,33], while eight of the 10 studies (80.0%) had a statistically significant improvement in CDVA post-CXL [20,22,26,28 && , 30,31,33,35]. Kmax significantly improved in all but one study [25] through the follow-up period.…”
Section: Acceleratedmentioning
confidence: 94%
“…We evaluated 10 studies exploring long term outcomes of accelerated, epithelium-off CXL for progressive KCN [20,22,23,25,26,28 && , 30,31,33,35]. Compared to the standard of 3 mW/cm 2 for a total of 30 min, studies had irradiation protocols of 9 mW/cm 2 for 10 min, 18 mW/cm 2 for 5 min, or 30 mW/cm 2 for 4 min.…”
Section: Acceleratedmentioning
confidence: 99%